Establishing a Diphtheria Toxin-sensitive system for cell ablation within the embryonic small intestine in mouse - Jesus, Ana Patrícia Martins de (2016)
The mouse small intestine possesses a highly complex structure with finger-like protrusions – villi – surrounded by invaginations called the crypts of Lieberkühn. Until it reaches its mature form, the embryonic small intestine undergoes a series of morphological and molecular changes. However, little is known about the molecular program involved in the development and establishment of the mouse small intestine. Id2, an inhibitor of DNA binding and differentiation, has been found to play a role in several biological processes, such as stem cell maintenance and tumorigenesis, and is a plausible candidate to be involved in the mechanisms mentioned above. The present study investigated the possible Id2 role in the development of the mouse small intestine through the ablation of the Id2+ cell population via Diphtheria Toxin (DT). The work conducted aimed to establish a DT-sensitive cell system for the ablation of the Id2+ cell population in the mouse embryonic small intestine, and compare the genetic profiles between sorted Id2+ epithelial iDTR- and iDTR+ cell populations. It was also proposed to evaluate the contribution of Id2 in the emmergence of the Lgr5+ cell population. Upon treatment of the embryos with DT, apoptosis was detected by immunohistochemistry targeting γH2AX in the iDTR+ embryos, with changes in the morphology of the iDTR+ embryonic small intestine also being showed by hematoxylin and eosin staining. Furthermore, upon cell sorting, Id2+ cells were found to be reduced when compared to control. Gene expression of the sorted cells by qPCR also showed a decrease in Id2 levels. Analysis of the high-red iDTR+ cell population by qPCR of a panel of genes – Lgr5, PUMA, Ascl2, Wnt6, Wnt11, Sfrp5, Rspo1, Rspo3, Snai2, Smoc2, Id1, Id3, Kcnq1, Kcne3, TBP, St8sia3, Slc2a3, OneCut2 – suggests that this cell population acquires proliferative and stem cell characteristics. The analysis of the non-red iDTR+ cells genetic profile also suggests a proliferative character.